Oxford handbook of general practice - Simon, Chantal; Everitt, Hazel; Dorp, Francoise van; Burkes, Matt (Oxford University Press, 2014)
Covering the whole of general practice, with hands-on advice from experienced practitioners, this essential handbook provides rapid access to information to help with any day-to-day problems which might arise in general practice. The handbook also includes quick reference practical management boxes for pediatric and elderly patients, a plate section of color images, and reference to online guidelines and resources.